Anatomical and Immunocoverage Observations on SuSy, C4H, and Pectate Lyase Family Protein Down-regulated Aspens Genotypes - David Sandquist (BioResources, 2015)
This study aims to complement previous studies on down-regulation of sucrose synthase and cinnamate 4-hydroxylase in hybrid aspen (Bjurhager et al. 2010; Gerber et al. 2014) with a quantitative anatomical comparison (Sandquist et al. 2015). The main focus was placed on evaluating quantitative modifications to fiber morphology and lignin composition. This was achieved by combining results from light-, electron-, and UV-microscopy together with histochemical staining. Overall there was good agreement between the morphological results in this study compared to the previously published chemical and physical reports, particularly on cinnamate 4-hydroxylase down-regulated aspen. The previously reported statistical correlations between fiber lumen area and plant diameter, and fiber length and tree height (Sandquist et al. 2015) have been further refined. Knock-down of genes coding for biologically important proteins such as sucrose synthase and cinnamate 4-hydroxylase had broad spanning morphological impacts. Down-regulated sucrose synthase genotype showed significantly reduced fiber development, possibly with altered S/G ratio. Down-regulated cinnamate 4-hydroxylase genotype showed an overall reduction of lignin in fibers as indicated from both chemical staining and UV-microscopy measurements. Down-regulated pectate lyase genotype showed no overall significant effects on fiber morphology, ultrastructural, nor lignin staining.